Membumikan Misi Kristen Melalui Pendidikan di Tanah Papua - Kainara, Semi Darius; Sarira, Ratmia; Sugiarsi, Ester (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
The purpose of this study is to provide understanding to Christians, churches, and Christian teachers in particular so that in every teaching they can carry out the great commission as the mission of the Lord Jesus through Education, especially in Papua , by making all nations disciples of Christ. Mission has the understanding that the way of salvation that God has given mankind is obtained in all the duties and responsibilities of His church. So mission encompasses the entire church's efforts to help the world experience deliverance from the bondage of sin and lead people to eternal life through faith and knowledge of Jesus Christ as the only way of salvation. Likewise, Education has a fairly broad meaning. In relation to mission, education can be interpreted as the efforts of Christian teachers to guide and direct students to the knowledge of Christ. The method used in this study is a descriptive qualitative method in which the author describes each observation and interview results obtained. The author focuses the location specifically on